The Effects of Green Technology, Clean Energy, and Green Finance on Faith-Based Investments: Evidence from Islamic Stock Markets - Gülfen Tuna; Zülküf Çevik (Türkiye İslam İktisadı Dergisi)
This study examines the long-term relationship between Islamic Stock prices, faith-based investments, green technology, clean energy, and green finance. The variables used in the study are the Clean Energy Index for clean energy, Green Bond Index for green finance, the Renewable Energy and Clean Technology Index for green technology and the Islamic Market Index for Islamic Stocks’ closing prices, as explained by S&P. The utilized research model is the NARDL model, and the findings reveal a cointegration relationship between faith-based and green finance instruments. Green finance instruments are unsuitable for the research period to be used as a safe-haven or effective diversification instrument for faith-based portfolios. Comprehending faith-based investments’ relationship with other green finance assets is critical in supporting sustainable development with financial market instruments, which provide environmental and societal benefits. As a result, apprehending the relationship between faith-based investments and green finance instruments can contribute to increasing social and environmental responsibility awareness in financial markets. The study’s outcomes hold significance in understanding how investors in financial markets react to positive and negative shocks, estimating these effects, efficiently managing portfolios comprising green financial assets and faith-based investments, and formulating an appropriate investment strategy.